Parâmetros hematológicos e toxicológicos em amostras de sangue de doadores fumantes e efeitos da nicotina in vitro - Silva, Valério Batista Melo da (2006)
Hemotherapy services in the Brazil are regulated according to the RDC-153. In general, smokers presented HT and Hb levels inside of the reference values to blood donations. Considering that reference values are in ample zone, this work studied the quality of blood utilized to donation in relations to hematologic parameters and two blood enzyme activities, PBG-synthase and cholinesterase. Besides, we also investigated the sensitivity of these enzymes to nicotine in vitro. These experiments may be explanatory as regard possible use of these enzymes as biomarkers to this agent since they are sensitive to oxidant and insecticides compounds respectivily. For in vivo experiments, thirty blood samples were divided in three groups according to smoke habit from donators: NF - non smoker, F10 - smoker of 10±5 cigarettes/day and F20 - smoker of 20 or more cigarettes/day. For in vitro, only samples from not smoker donators were used. The results demonstrated that HT and Hb levels in the F20 group were significantly higher than others. The COHb levels were significantly higher in the both smoker groups, F10 and F20, than control group (NF). In relation to PBG-synthase and cholinesterase, smoke habit did not alter their activities. The F20 group presented a short decrease in PBG-synthase activity and in reactivation index. The cholinesterase activity from F20 group was higher (18%) than other groups, but not significantly. The in vitro results demonstrated that to PBG-synthase, only concentrations higher than 10 mM were able to inhibit the its activity, and the mechanism involved in these inhibition seems to be not related to oxidative effects since the DTT was not able to recover the activity. Total blood AChE is much more sensitive to nicotine than the plasma ChE, since the IC50 for these activities were 3 and 22 mM of nicotine, respectively. Taking as a whole, these results show the low sensitivity of these enzymes to smoke and to nicotine. However, it is need to consider that all experiments were conducted with substrate concentration at levels of saturation and this is not a physiologic condition. This fact is important mainly in relation to blood AChE since the competitive component is involved in this inhibition; thus, the endogenous inhibition can occur even when this not appear in the in vitro assays. Then, according to these data, we suggest more attention as to quality of human blood utilized in the hemoterapy services in the Brazil.